2019
DOI: 10.3390/nano9121748
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Calcium Phosphate Desensitising Agents in Dental Hypersensitivity Over 24 Weeks of Clinical Evaluation

Abstract: Background: Calcium phosphate-based compounds are used to treat dental hypersensitivity (DH). Their long-term clinical behaviour needs further research. This study compared the 24-week effectiveness of Teethmate Desensitizer (TD), a pure tetracalcium phosphate (TTCP) and dicalcium phosphate dihydrate (DCPD) powder/water, to that of Dentin Desensitizer (DD), and Bite & White ExSense (BWE), both of calcium phosphate crystallites. Methods: A total of 105 subjects were selected. A random table was utilised to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…A total of 7515 articles were excluded after reading titles and/or abstracts, 12 records were excluded since reports were not retrieved, 57 records from database registers and 18 identified through other methods were read and analyzed in their full-text, and 55 records were excluded for reasons such as not good drugs tested ( n = 34), in vitro studies ( n = 11), or study on tooth decay ( n = 10), as shown in Figure 1 . Twenty records met the inclusion criteria and were included in the systematic review: Poliakova et al, 2022 [ 30 ], Alharith et al, 2021 [ 31 ], Amaechi et al, 2021 [ 32 ], Eyuboglu et al, 2020 [ 33 ], Usai et al, 2019 [ 34 ], Amaechi et al, 2018 [ 35 ], Ameen et al, 2018 [ 36 ], Anand et al, 2018 [ 37 ], Vano et al, 2017 [ 38 ], De Oliveira et al, 2016 [ 39 ], Wang et al, 2016 [ 40 ], Gopinath et al, 2015 [ 41 ], Jena et al, 2015 [ 42 ], Mehta et al, 2015 [ 43 ], Naoum et al, 2015 [ 44 ], Mehta et al, 2014 [ 45 ], Porciani et al, 2014 [ 46 ], Vano et al, 2014 [ 47 ], Ghassemi et al, 2009 [ 48 ], and Geiger et al, 2003 [ 49 ]. The selection process has been detailed in the attached PRISMA flowchart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 7515 articles were excluded after reading titles and/or abstracts, 12 records were excluded since reports were not retrieved, 57 records from database registers and 18 identified through other methods were read and analyzed in their full-text, and 55 records were excluded for reasons such as not good drugs tested ( n = 34), in vitro studies ( n = 11), or study on tooth decay ( n = 10), as shown in Figure 1 . Twenty records met the inclusion criteria and were included in the systematic review: Poliakova et al, 2022 [ 30 ], Alharith et al, 2021 [ 31 ], Amaechi et al, 2021 [ 32 ], Eyuboglu et al, 2020 [ 33 ], Usai et al, 2019 [ 34 ], Amaechi et al, 2018 [ 35 ], Ameen et al, 2018 [ 36 ], Anand et al, 2018 [ 37 ], Vano et al, 2017 [ 38 ], De Oliveira et al, 2016 [ 39 ], Wang et al, 2016 [ 40 ], Gopinath et al, 2015 [ 41 ], Jena et al, 2015 [ 42 ], Mehta et al, 2015 [ 43 ], Naoum et al, 2015 [ 44 ], Mehta et al, 2014 [ 45 ], Porciani et al, 2014 [ 46 ], Vano et al, 2014 [ 47 ], Ghassemi et al, 2009 [ 48 ], and Geiger et al, 2003 [ 49 ]. The selection process has been detailed in the attached PRISMA flowchart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up range varied from immediately to 6 months. Most of the studies performed a 4-week follow-up phase [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, the short application time and use of noncorrosive, pH-neutral or alkaline gels is recommended [ 47 ]. Overall, side effects can be minimised with modern desensitising materials [ 48 , 49 ] and techniques [ 50 , 51 ]. Notwithstanding, a general review of the safety of tooth whitening has been published and it is reassuring that the number of clinically reported adverse effects or incidents after bleaching is relatively low [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The paste could have stayed on the surface of the tubule, possibly delivering Ca-P particles into the tubules. The tubular ratio and hydraulic pipeline could have been reduced, thus explaining the reduced pain and the drop of VAS values immediately on the application of the agent [ 44 ].…”
Section: Discussionmentioning
confidence: 99%